2002
DOI: 10.1002/1522-2683(200202)23:2<203::aid-elps203>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Repartition effect of aromatic polyaniline coatings on the separation of bioactive peptides in capillary electrophoresis

Abstract: The capillary walls of fused-silica capillary electrophoresis (CE) columns were modified with a thin film of polyaniline (PANI), providing open-tubular columns with a stable coating containing aromatic groups and amine functionalities. Fast and efficient separations were observed for small bioactive peptides under acidic conditions on PANI-coated columns. The mechanism of separation is based on hydrophobic interactions between the analytes and the polymeric matrix. Good reproducibility was observed from run-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
(21 reference statements)
2
10
0
Order By: Relevance
“…The same held true in case of polyaniline coatings for the separation of peptides [31]. The possible explanation is a mechanism of separation for the APBA polymer that acts through interactions between the analyte and the polymer coating, as already supposed in case of polyaniline-modified columns.…”
Section: Recognition Of Diastereoisomers Of Ascorbic Acid On Abpa Colsupporting
confidence: 59%
“…The same held true in case of polyaniline coatings for the separation of peptides [31]. The possible explanation is a mechanism of separation for the APBA polymer that acts through interactions between the analyte and the polymer coating, as already supposed in case of polyaniline-modified columns.…”
Section: Recognition Of Diastereoisomers Of Ascorbic Acid On Abpa Colsupporting
confidence: 59%
“…This provided evidence of preferred FN and BSA protein adsorption on PANI films and that the nanosurface properties (i.e., greater surface nanoroughness with increased surface energy) of PANI films coating acted as a favorable environment for protein adsorption. Some investigations into electric potential assisted deposition of proteins reported that protein adsorption was usually spontaneous, and the electrostatic interactions naturally played an important role [28,29]. During the electrical stimulation, protein adsorption behavior could be expected to depend on the electrostatic interaction between the negatively charged proteins and the electrical field generated on the PANI films.…”
Section: Resultsmentioning
confidence: 99%
“…Several aspects of current work on CE biosensors are summarized herein. An aromatic polyaniline-coated CE chip has been developed for separation of bioactive peptides [186] and a PPF-coated CE chip has been developed for the separation of protein, cytochrome c (pI 9.6), hemoglobin (pI 7.0), and phycocyanin (pI 4.7) [123]. Laserinduced fluorescence (LIF) is the most common detection system for microchips, because of its high sensitivity.…”
Section: Microfluidic Chipsmentioning
confidence: 99%